2019
DOI: 10.1002/ppsc.201800507
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Physiological Stability and Long‐Term Toxicity/Biodegradation In Vitro/In Vivo of Monodispersed Glycerolphosphate‐Functionalized Bioactive Glass Nanoparticles

Abstract: Monodispersed bioactive glass nanoparticles (BGNs) have received much attention in various biomedical applications such as tissue regeneration, drug/gene delivery, bioimaging, and cancer therapy. However, the poor dispersion stability of BGNs in a physiological environment has limited their wide biomedical applications. The long‐term in vitro/in vivo toxicity and biodegradation of BGNs are also not clear. Monodispersed glycerolphosphate‐functionalized BGNs (GP‐BGN) are synthesized and their stability under phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…However, the inorganic nanoparticles-incorporated PLGA scaffolds still show low bone-bonding activity and angiogenesis ability. Micro-nano bioactive glass (MNBG) as a kind of bioactive biodegradable biomaterial (Hu et al, 2013; Xue et al, 2019), has a good ability of mineralization forming into hydroxyapatite and excellent biological activity (Rahaman et al, 2011; Bachar et al, 2016). Furthermore, the ions (Si 4+ and Ca 2+ ) released from MNBG have therapeutic functions, which can stimulate cell proliferation and the expression of osteogenesis and angiogenesis related genes, eventually to facilitate osseointegration (Xynos et al, 2001; Gorustovich et al, 2010; Gerhardt et al, 2011; Hoppe et al, 2011; Cong et al, 2015; Zhang et al, 2016; Dashnyam et al, 2017; Mao et al, 2017; Kargozar et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, the inorganic nanoparticles-incorporated PLGA scaffolds still show low bone-bonding activity and angiogenesis ability. Micro-nano bioactive glass (MNBG) as a kind of bioactive biodegradable biomaterial (Hu et al, 2013; Xue et al, 2019), has a good ability of mineralization forming into hydroxyapatite and excellent biological activity (Rahaman et al, 2011; Bachar et al, 2016). Furthermore, the ions (Si 4+ and Ca 2+ ) released from MNBG have therapeutic functions, which can stimulate cell proliferation and the expression of osteogenesis and angiogenesis related genes, eventually to facilitate osseointegration (Xynos et al, 2001; Gorustovich et al, 2010; Gerhardt et al, 2011; Hoppe et al, 2011; Cong et al, 2015; Zhang et al, 2016; Dashnyam et al, 2017; Mao et al, 2017; Kargozar et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Silicon‐based bioactive biomaterials such as bioactive glass (BG, typical composition: SiO 2 ‐CaO‐P 2 O 5 ), have been extensively used for bone tissue repair, owing to its good biocompatibility, biodegradation, tissue regeneration ability . Monodispersed BG nanoparticles (BGNs) with enhanced biological performance were also developed for bioimaging, osteogenic differentiation of stem cells, drugs, and gene delivery . Recently, it was shown that nanoscale BG could enhance chronic wound healing through improving the angiogenesis .…”
Section: Introductionmentioning
confidence: 99%
“…Monodispersed BGNs and nanoscale silicon‐based biomaterials could also efficiently enhance the osteogenic differentiation of osteoblasts and bone marrow stem cells 31–33. Recent years, our group further found that monodispersed BGNs could induce the osteogenic differentiation of adipose mesenchymal stem cells (ADMSCs) through activating the TGF‐beta signaling pathway, and the molybdenum‐based branched BGNs could also promote the osteogenic differentiation of ADMSCs 34,35. However, the monodispersed BGNs without surface modification are easy to be aggregated during the using process.…”
Section: Introductionmentioning
confidence: 98%